2015
DOI: 10.1534/genetics.115.178525
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Gene Disruption by Ectopic Induction of DNA Elimination in Tetrahymena

Abstract: Tetrahymena is a useful eukaryotic model for biochemistry and molecular cell biology studies. We previously demonstrated that targeted ectopic DNA elimination, also called co-Deletion (coDel), can be induced by the introduction of an internal eliminated sequence (IES)-target DNA chimeric construct. In this study, we demonstrate that coDel occurs at most of the loci tested and can be used for the production of somatic gene KO strains. We also showed that coDel at two loci can be simultaneously induced by a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 25 publications
(27 reference statements)
2
39
0
Order By: Relevance
“…1; Galati et al, 2014). To investigate the effect of Cro1p loss on SFs, T. thermophila CRO1 was knocked out in the T. thermophila macronucleus using CoDel (Hayashi and Mochizuki, 2015). Successful CRO1 knockout was confirmed by the loss of CRO1 genomic DNA and CRO1 transcripts (Fig.…”
Section: Cro1p Promotes Elevated Ciliary Force-induced Sf Elongationmentioning
confidence: 99%
“…1; Galati et al, 2014). To investigate the effect of Cro1p loss on SFs, T. thermophila CRO1 was knocked out in the T. thermophila macronucleus using CoDel (Hayashi and Mochizuki, 2015). Successful CRO1 knockout was confirmed by the loss of CRO1 genomic DNA and CRO1 transcripts (Fig.…”
Section: Cro1p Promotes Elevated Ciliary Force-induced Sf Elongationmentioning
confidence: 99%
“…To eliminate background autophagic DNA fragments, we created somatic knockout strains for the autophagy-related 8 isoform 2 gene ( ATG8-2 ), which encodes a central component of the Tetrahymena autophagosome (Figure 8A; Liu and Yao, 2012), using the co-Deletion technique (described in Hayashi and Mochizuki, 2015). Diagnostic PCR for the ΔATG8-2 strains of different mating types showed that ATG8-2 genomic loci were completely deleted (Figure 8B).…”
Section: Resultsmentioning
confidence: 99%
“…The post-meiotic signal in this mutant was completely absent in a triple mutant ( TOP2gi::SPO11i::ΔATG8-2 ; Figure 8E). These results show that programmed PM-DSBs are present in Tetrahymena , suggesting that PM-DSB formation requires both Top2g and Spo11.
10.7554/eLife.26176.016Figure 8. ATG8-2 gene knockout eliminates background DNA fragments resulting from autophagic degradation of unselected pronuclei.( A ) Schematic representation of ATG8-2 knockout strains by co-Deletion (as described in Hayashi and Mochizuki, 2015), confirmed by diagnostic PCR. The PCR primer set is indicated by arrows.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a rapid method for MAC gene knockouts has been developed that does not depend on homologous recombination (Hayashi and Mochizuki 2015;Noto et al 2015). Codeletion (CoDel) harnesses the endogenous mechanism for IES DNA elimination during MAC development to remove 1 kb of a gene of interest.…”
Section: Reverse Genetics: Analysis Of Identified Genesmentioning
confidence: 99%